Genetic diversity in African yam bean [Spenostylis stenocarpa (Hochst ex A. Rich.) Harms] collection - Ebiti, E.K. (University of Ibadan, 2023)
African Yam Bean (AYB) is an underutilized legume with great potential of providing an inexpensive and sustainable solution to malnutrition and food insecurity in Sub-Saharan Africa. However, its genetic variability is not yet fully exploited and documented. To enhance the full exploitation and improvement of the crop, there is a need for knowledge of its genetic diversity. This research was therefore carried out to assess the genetic diversity in AYB germplasm collection using agro-morphological traits, genetic markers, nutritional, anti-nutritional, and mineral composition. Thirty AYB accessions were evaluated during the 2021 cropping season at the International Institute of Tropical Agriculture (IITA). The field experiment was laid out in a Randomized Complete Block Design with three replicates. The accessions were evaluated for 28 agro- morphological and 16 categorical characters using the IITA Reference Guide. Seeds and tubers of the AYB accessions were evaluated for nutritional values using the Association of Official Analytical Chemists (A.O.A.C) method of analysis. Accessions were genotyped by DArTseq high-depth technology. A total of 5,142 Single Nucleotide Ppolymorphism (SNP) markers were generated and quality control was performed on the basis of Call Rate <0.70, marker reproducibility (RepAvg) <0.95, >10% missing values, and <0.01 minor allele frequency. A total of 1,805 high-quality and genome-wide DArTseq SNP markers were retained after quality control (QC) and used for the diversity study. Data were subjected to analysis of variance at α0.05, while cluster analysis was performed using R-package. There were significant difference among the AYB accessions for the traits evaluated. The earliest days to peduncle initiation (49 days), days to first flowering (64 days), and 50% flowering (73 days) were observed in TSs-519. Also, the highest pod weight per plant (59.64 g), number of seeds per pod (94), and seed weight per pod (28.08 g) were observed in TSs-519. Accessions TSs-104 had the earliest days to pod maturity (122 days). Moisture content (MC) in AYB tubers ranged from 10.25±0.03% (TSs-104) to 10.78±0.14% (TSs-130), while MC in AYB seeds ranged from 10.26±0.13% (TSs-674) to 10.64±0.13% (TSs-561). Protein content (PC) in AYB tubers ranged from 9.69±0.09% (TSs-130) to 9.88±0.08% (TSs-104). Whereas, the PC in the seeds ranged from 19.91±0.50% (TSs-561) to 24.40±0.33% (TSs-562). Carbohydrate content (CC) in AYB tubers ranged from 71.23±0.50% (TSs-104) to 72.13±0.56% (TSs-130), while CC in AYB seeds ranged from 48.03±0.84% (TSs-642) to 58.81±0.80% (TSs-613). Trypsin inhibitor in AYB tubers ranged from 6.48±0.70 mg/g (TSs-104) to 7.47±0.70 mg/g (TSs-130), while trypsin inhibitor in AYB seeds ranged from 1.987±0.00 mg/g (TSs-634) to 38.30±0.70mg/g (TSs-636). Zinc content in AYB seeds ranged from 23.28±0.56 ppm (TSs-519) to 31.40±0.41 ppm (TSs-642). Heterozygosity of 7.79% was observed in the AYB population. The AYB accessions were grouped into four main clusters based on the agro-morphological traits and 1,805 SNP markers. Genetic diversity exists among the African yam bean accessions based on morphological traits, nutritional, anti-nutritional, and mineral composition. The accessions were also highly discriminated based on the genetic markers.